2016
DOI: 10.1089/neu.2014.3774
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Attenuates Traumatic Brain Injury: Induced Neuronal Hyperexcitability in Supragranular Layers of Sensory Cortex

Abstract: We have previously demonstrated that traumatic brain injury (TBI) induces significant long-term neuronal hyperexcitability in supragranular layers of sensory cortex, coupled with persistent sensory deficits. Hence, we aimed to investigate whether brain plasticity induced by environmental enrichment (EE) could attenuate abnormal neuronal and sensory function post-TBI. TBI (n = 22) and sham control (n = 21) animals were randomly assigned housing in either single or enriched conditions for 7-9 weeks. Then, in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…39,[42][43][44] Animal studies have shown that TBI induces long-term neuronal hyperexcitability in the sensory cortex. 39,45 PTSD is commonly associated with alterations in areas of the frontal cortex, hippocampus, amygdala, and overall reductions in neuronal volume. [46][47][48] In addition, the amygdala, which is dysfunctional in PTSD, influences sensory processing through projections to neuromodulatory centers from the forebrain and brainstem, which guide attention, mood and adjust sensory responses to the demands of the environment and internal state of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…39,[42][43][44] Animal studies have shown that TBI induces long-term neuronal hyperexcitability in the sensory cortex. 39,45 PTSD is commonly associated with alterations in areas of the frontal cortex, hippocampus, amygdala, and overall reductions in neuronal volume. [46][47][48] In addition, the amygdala, which is dysfunctional in PTSD, influences sensory processing through projections to neuromodulatory centers from the forebrain and brainstem, which guide attention, mood and adjust sensory responses to the demands of the environment and internal state of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous TBI studies (Alwis et al, , ; Carron et al, ; Johnstone et al, , , ), a standard rotarod test was used to assess sensorimotor function following injury. Grip strength and sensorimotor function are assessed by recording the maximum rotational speed at which the rats can maintain their position on the rotarod, a rotating cylinder comprising of 18 stainless steel rods (1 mm diameter).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, previous research showed that there were no differences in the outcomes of MWM or elevated plus maze (EPM) between the sham-EE group and sham group. 13 , 69 , 70 Moreover, studies also revealed no differences in the level of BDNF and inflammatory factors between the sham-EE group and sham group. 69 , 70 , 90 Therefore, we speculated that a sham-EE group might show the same results as the Sham group when compared with the other experimental groups.…”
Section: Discussionmentioning
confidence: 90%
“…11,12 For example, sensory and memory impairment after traumatic brain injury (TBI) can be relieved by EE, possibly via cortical excitability and reorganization. [13][14][15][16][17] EE was also shown to prevent stroke-induced learning and memory disorder. [18][19][20] Moreover, in models of ethanol binge-drinking or perinatal asphyxia, accumulating evidence points to the positive effects of EE on learning and memory deficits.…”
Section: Introductionmentioning
confidence: 98%